1998
DOI: 10.1046/j.1468-2982.1998.1805283.x
|View full text |Cite
|
Sign up to set email alerts
|

S-fluoxetine in the prophylaxis of migraine: a phase II double-blind randomized placebo-controlled study

Abstract: S-fluoxetine is the long-acting enantiomer of the racemic antidepressant serotonin reuptake inhibitor. Sixty-five patients needing migraine prophylaxis were recruited into a phase II, double-blind, placebo-controlled trial. After a 1-month placebo run-in, 53 patients met entry criteria with regard to attack frequency and were randomized, 27 to S-fluoxetine and 26 to matching placebo. Three failed to start treatment and there were 17 early discontinuations, 9 from S-fluoxetine, 8 from placebo, at similar times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 10 publications
1
43
0
3
Order By: Relevance
“…Of these, only fluvoxamine does not possess any chiral centres; FLU and CIT are marketed or under study both as racemates and single enantiomers ((R)-FLU and escitalopram), while paroxetine and SRT are marketed as single enantiomers. seems to be quite similar [18] (the (S)-enantiomer also seems to have antimigraine activity [19]). On the other hand, the enantiomers of the main active metabolite of FLU (norfluoxetine) have very different pharmacological and pharmacokinetic properties [20].…”
Section: Selective Serotonin Reuptake Inhibitorsmentioning
confidence: 97%
“…Of these, only fluvoxamine does not possess any chiral centres; FLU and CIT are marketed or under study both as racemates and single enantiomers ((R)-FLU and escitalopram), while paroxetine and SRT are marketed as single enantiomers. seems to be quite similar [18] (the (S)-enantiomer also seems to have antimigraine activity [19]). On the other hand, the enantiomers of the main active metabolite of FLU (norfluoxetine) have very different pharmacological and pharmacokinetic properties [20].…”
Section: Selective Serotonin Reuptake Inhibitorsmentioning
confidence: 97%
“…An additional, placebo-controlled trial reinforced the potential benefit of this agent in the longterm treatment of migraine [d 'Amato et al, 1999]. The S-isomer of fluoxetine may also have clinical benefit in migraine prevention [Steiner et al, 1998]. A comparative trial of venlafaxine, an SNRI antidepressant, with the tricyclic amitriptyline showed both agents to be equally effective in reducing attack frequency [Bulut et al, 2004].…”
Section: Antidepressantsmentioning
confidence: 99%
“…I dati disponibili indicano un moderato livello di efficacia nella cefalea cronica giornaliera e una mancanza di efficacia nel controllare i sintomi dell'emicrania [167,168].…”
Section: Dolore Cronicounclassified
“…Quest'attività sembra essere dovuta all'isomero S-fluoxetina. [168] Disfunzione sessuale: eiaculazione prematura La fluoxetina è efficace nel trattamento sintomatico della eiaculazione prematura. I risultati obiettivi (prolungamento da 1 a 6-10 minuti dell'intervallo pre-eiaculatorio intravaginale) si possono osservare dopo almeno due settimane di trattamento.…”
Section: Dolore Cronicounclassified